2020
DOI: 10.1101/2020.02.26.965178
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sp8regulatory function in the limb bud ectoderm

Abstract: Sp8 and Sp6 are two closely related Sp genes expressed in the limb ectoderm where they regulate proximo-distal and dorso-ventral patterning. Mouse genetics revealed that they act together in a dose-dependent manner but with Sp8 making a much greater contribution. Here, we combine ChIP-seq and RNA-seq genome-wide analyses to investigate the Sp8 regulatory network and mechanism of action. We find that Sp8 predominantly binds to putative distal enhancers to activate crucial limb patterning genes, including Fgf8, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Indeed, physical interactions were detected between Sp8 and Dlx5 and between Sp6 and Dlx5. However, the functional outcome of the interaction seems to be complex and likely depends on the availability of the interacting TFs [ 27 ]. Sp6 ChIP-seq analysis in developing mouse teeth similarly demonstrated that an AT-rich motif was enriched in the Sp6-bound genomic regions [ 28 ].…”
Section: The Mode Of Sp7 Action: How Does It Contribute To the Transc...mentioning
confidence: 99%
“…Indeed, physical interactions were detected between Sp8 and Dlx5 and between Sp6 and Dlx5. However, the functional outcome of the interaction seems to be complex and likely depends on the availability of the interacting TFs [ 27 ]. Sp6 ChIP-seq analysis in developing mouse teeth similarly demonstrated that an AT-rich motif was enriched in the Sp6-bound genomic regions [ 28 ].…”
Section: The Mode Of Sp7 Action: How Does It Contribute To the Transc...mentioning
confidence: 99%
“…Interestingly, recent ChIP‐seq studies suggest that Sp7's “non‐canonical” mode of action is also shared with a few other Sp family members; given that Sp8‐bound regions enriched an AT‐rich motif as well as a GC‐rich motif in the limb ectoderm, Sp8 is likely to utilize both “canonical” and “non‐canonical” modes of action during limb patterning 58 . In addition, Sp6‐bound regions showed enrichment of an AT‐rich motif in mesenchymal cells of mouse developing teeth 59 …”
Section: Mode Of Sp7 Action In the Osteoblast Lineagementioning
confidence: 99%